LEARNING CURVE OF ENDOSCOPIC RETROGRADE CHOLANGIO PANCREATOGRAPHY (ERCP) IN A DEVELOPING COUNTRY: A REVIEW OF THE FIRST 300 PROCEDURES - De zoysa, M.I.M.; Samarasekera, D.N. (My University, 2012)
ERCP is a technically demanding procedure which can cause substantial complications. The objective of this study was to analyze the problems encountered, lessons learnt, success rate and complications during the first 300 procedures.